TEORI PENGOLAHAN INFORMASI: PERSPEKTIF PENDIDIKAN - Rafiqa Rafiqa (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2015)
Information management theories emphasize that transformation and information ideology through cognition sistem. the important one that informations was present in front on students have to clear and easy so they can correlated the new information with old information in their memory, the they understand how to use that knowledge. The aimed of this paper will help the plan of teaching-learning process run well, so it will develop the knowledge and then students understand well about that knowledge. The teacher had better prepare an introduction organizers and symbols to help students to memorize an informations when they need it to minimize cognition working. Theories of information management focused on study about attention, perception, code, storage and conclude the knowledge. Information management had influenced by communication and technology development.